Validation of the Short Self-Regulation Questionnaire for Taiwanese College Students (TSSRQ) - Chen, Yang-Hsueh; Lin, Yu-Ju (Frontiers in Psychology, 2018)
While self-regulation has long been recognized as an important characteristic of an individual, instruments assessing the general aptitude of self-regulation remain limited especially in Asian countries. This study re-validated Carey, Neal, and Collins’ (2004) Short Self-Regulation Questionnaire based on a national sample of Taiwanese college students (N=1,988). Item analysis, exploratory factor analysis, and confirmatory factor analysis yielded 22 items in five internally consistent factors. Descriptive findings showed that, a lack of proactiveness and volitional control, and a decrease of self-regulation throughout the college span appeared to be an overarching problem among Taiwanese college students. Furthermore, male students achieved lower self-regulation scores than female ones, and students in Services and STEM-related majors are in the need of self-regulation enhancement. Due to the generic measurement of individuals’ self-regulation traits, the Taiwanese Short Self-regulation Questionnaire (TSSRQ) can be flexibly applied to various contexts and used to deal with different issues beyond learning such as college students’ Internet or smartphone addiction. Through this study, we hope the validated TSSRQ can promote studies on self-regulation and associated antecedents and outcomes, in turn leveraging college students’ life adjustment and well-being.